Reinsemination intervals after timed artificial insemination or estrus-detected inseminations - Jeffrey S. Stevenson (Kansas Agricultural Experiment Station Research Reports, 2012)
The objective was to quantify the reinsemination intervals of lactating dairy cows that were either inseminated at estrus or received a timed AI (TAI) at first service. Cows in Experiment 1 were enrolled in a TAI program before first AI after calving. Cows detected in estrus after 50 days in milk (DIM) were inseminated, whereas the remainder continued in the TAI program and were inseminated as scheduled. Cows in Experiment 2 also were enrolled in a TAI program and were inseminated accordingly at first service after calving. On day 7 after TAI, cows were assigned randomly to receive either saline (control) or 1,000 IU human chorionic gonadotropin (hCG) to induce accessory luteal structures (corpora lutea) in an attempt to improve pregnancy outcome. First-repeat insemination dates were recorded for all cows after the initial AI and grouped as<18>days, 18 to 25 days, or>25 days since first AI. More cows in Experiment 1 that were inseminated at estrus returned to estrus before 25 days than TAI cows and during summer months had shorter average return intervals by 1.7 days. More cows in Experiment 2 that received saline and had no accessory luteal structures also returned to estrus before 25 days than cows receiving hCG. Equal proportions of saline and hCG-treated cows (25%) in Experiment 2 had retained at least one of their original luteal structures until day 28 after TAI, but were not pregnant at day 32. Of those nonpregnant cows that retained luteal structures, average concentrations of pregnancy-specific protein B (BioPRYN test) concentrations were slightly elevated, but failed to retain the embryos to day 32 after AI. Furthermore, progesterone concentrations of these cows that lost their embryos were compromised compared with pregnant cows by day 21 after AI. Regardless of the number of luteal structures after first insemination, 25% were retained up to 28 days after AI, indicating pregnancy had occurred but embryo loss occurred between pregnancy recognition (day 15) and days 28 to 32 after insemination. Cows receiving TAI also had longer reinsemination intervals than cows inseminated at estrus, a phenomenon that is exaggerated during summer heat stress.; Dairy Day, 2012, Kansas State University, Manhattan, KS, 2012; Dairy Research, 2012 is known as Dairy Day, 2012
Keywords: Dairy Day; 2012; Kansas Agricultural Experiment Station contribution; no. 13-030-S; Report of progress (Kansas Agricultural Experiment Station and Cooperative Extension Service); 1075; Dairy cows; Human chorionic gonadotropin; Estrus; Reinsemination; Embryo loss